PENGARUH BIAYA OPERASIONAL PENDAPATAN OPERASIONAL DAN NET PROFIT MARGIN TERHADAP RETURN ON ASSETS PADA BANK BNI TBK - Nurwita Nurwita; Diane Mutia Burhan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of operational costs on operational income (BOPO) and net profit margin (NPM) on return on assets (ROA) at Bank BNI Tbk, both partially and simultaneously. The research method uses a quantitative method with a descriptive approach and the data source used is secondary data in the form of Bank BNI Tbk's financial reports for a period of 10 years from 2013-2022, obtained from the Indonesian Stock Exchange (BEI) website which takes the balance sheet & profit and loss section and processed using SPSS version 25 software. Based on the research results, it shows that the BOPO variable partially has no effect on ROA which can be seen from t count -2.002 <ttable 2.306 with a significance level of 0.085>0.05 so the hypothesis shows that H01 is accepted and Ha1 is rejected, the NPM variable partially has a significant effect on ROA which can be seen from t count 6.016 > ttable 2.306 with a significance level of 0.001<0.05 so that the hypothesis shows that H02 is rejected Ha2 is accepted and the BOPO and NPM variables together have a significant effect on ROA at Bank BNI Tbk which can be seen from fcount 18.223>ftable 4.74 with a significance level of 0.002<0.05 so the hypothesis shows that H03 is rejected and Ha3 is accepted. In the coefficient of determination test results, it is explained that BOPO and NPM affect ROA simultaneously at 83.9%. Meanwhile, the remaining 16.1% is a value that is influenced by other factors outside the independent variable studied.